1976
DOI: 10.1088/0022-3727/9/5/017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of organic additives on the breakdown and gassing properties of mineral oils

Abstract: The effect of organic additive content on the direct voltage breakdown strength of degassed transformer oil and liquid paraffin is reported for a wide range of concentration of additives known to be effective gassing inhibitors. Their effect on the breakdown strength of oils saturated with hydrogen, nitrogen and oxygen is also reported. Measurements of the gassing properties of the oils were carried out for the same extended range of additive concentrations. The observed breakdown and gassing versus concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Contrary to Zaky and Hawley [6], Mathes and Rouse [8] reported that the addition of a small concentration of poly-aromatic compounds significantly reduces the dielectric strength of naphthenic oil in a point-to-sphere electrode arrangement under impulse voltage. This reduction in the breakdown voltage has been attributed to the streamer development and especially to the increase in the velocity of the streamers' propagation: the faster the streamer, the lower the dielectric strength.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Contrary to Zaky and Hawley [6], Mathes and Rouse [8] reported that the addition of a small concentration of poly-aromatic compounds significantly reduces the dielectric strength of naphthenic oil in a point-to-sphere electrode arrangement under impulse voltage. This reduction in the breakdown voltage has been attributed to the streamer development and especially to the increase in the velocity of the streamers' propagation: the faster the streamer, the lower the dielectric strength.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, it has been observed that several specific nanoparticles such as Fe 3 O 4 significantly enhance the dielectric strength of mineral oils [1][2][3][4][5]. Nevertheless, the results reported in the literature on the influence of aromatic additives on the breakdown voltage of insulating oils are contradictory [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PDIV is defined as the voltage in which the partial discharge (PD) is initiated above the threshold of 20 pC. Zaky et al [22] also attributed this behaviour to the addition of additives containing aromatic compounds into the insulation oil.…”
Section: Dielectric Strength and Oxidativ Estability Analysismentioning
confidence: 99%
“…However, another area of research which has been somewhat neglected and which could present another interesting line of research is that of molecular additives. Among the investigations dealing with these kinds of additives and their influence on the breakdown voltage (BDV) of insulating oils, the aromatic compounds [1]. Unfortunately, the reported results are contradictory [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%